Debating the Law, Creating Gender : Sharia and Lawmaking in Palestine, 2012-2018 - Schneider, Irene, (Women and Gender: The Middle East and the Islamic World ;, 2021)
In Palestine, family law is a controversial topic publicly debated by representatives of the state, Sharia establishment, and civil society. Yet to date no such law exists. This book endeavors to determine why by focusing on the conceptualization of gender and analyzing "law in the making" and the shifts in debates (2012-2018). In 2012, a ruling on khulʿ -divorce was issued by the Sharia Court and was well received by civil society, but when the debate shifted in 2018 to how to "harmonize" international law with Islamic standards, the process came to a standstill. These developments and the various power relations cannot be properly understood without taking into consideration the terminology used and redefined in these debates.